2021
DOI: 10.1007/s00464-021-08742-1
|View full text |Cite
|
Sign up to set email alerts
|

Warm and humidified insufflation gas during gynecologic laparoscopic surgery reduces postoperative pain in predisposed patients—a randomized, controlled multi-arm trial

Abstract: Background Postoperative pain remains a common problem in gynecologic laparoscopy, especially in head zone-related regions, triggered by intra-abdominal pressure during capnoperitoneum. Humidified and prewarmed insufflation gas may ameliorate pain and be beneficial. Methods This prospective randomized controlled parallel group multi-arm single-center study investigated the effects of temperature and humidity of insufflation gas on postoperative pain during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[18] Therefore, most of the techniques used to prevent PLSP or to reduce the incidence were based on reducing physical or chemical stimulation on the surface of the diaphragm. Studies have shown that discharging the remaining intraperitoneal gas by using passive drainage or active aspiration at the end of the procedure can reduce the CO 2 in the peritoneal cavity, [9] applying lung compmanipulation can squeeze out the gas, [23] using gas heating, lowing pneumoperitoneum pressure, [10] low inflation rate and even using gas-free laparoscopy can reduce body irritation, all of which can reduce the incidence of PLSP. Furthermore, PLSP was reduced by inhibition of pain signals itself with anti-inflammatory agents, such as local anesthetic for surface of diaphragm at the beginning or the end of surgery, [24] intraperitoneal infusion of dexmedetomidine, bupivacaine or hydrocortisone, [25] and intraperitoneal or intrathecal injection of clonidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Therefore, most of the techniques used to prevent PLSP or to reduce the incidence were based on reducing physical or chemical stimulation on the surface of the diaphragm. Studies have shown that discharging the remaining intraperitoneal gas by using passive drainage or active aspiration at the end of the procedure can reduce the CO 2 in the peritoneal cavity, [9] applying lung compmanipulation can squeeze out the gas, [23] using gas heating, lowing pneumoperitoneum pressure, [10] low inflation rate and even using gas-free laparoscopy can reduce body irritation, all of which can reduce the incidence of PLSP. Furthermore, PLSP was reduced by inhibition of pain signals itself with anti-inflammatory agents, such as local anesthetic for surface of diaphragm at the beginning or the end of surgery, [24] intraperitoneal infusion of dexmedetomidine, bupivacaine or hydrocortisone, [25] and intraperitoneal or intrathecal injection of clonidine.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Studies have shown that the incidence of PLSP can be decreased by reducing the pneumoperitoneum pressure, slowing down the speed of the injected gas, and using the heating gas which can reduce the stimulating effect of intraabdominal gas on the diaphragm. [9,10] We speculated that it was not only related to the reduction of intra-abdominal pressure, but probably also to the reduction of CO 2 concentration in blood. Therefore, this study was designded to obeserve the effect of intraoperative mild hyperventilation on the incidence of PLSP after LSG, to verify the above conjecture and provide a reference for reducing the occurrence of PLSP after such surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The trial design was tailored to evaluate the effect on body temperature and therefore did not include second-look laparoscopies which would have been necessary to answer the question of adhesion formation. The effect on postoperative pain was also investigated in this study and published before [15].…”
Section: Limitations and Strengthmentioning
confidence: 99%
“…Here, we present the results of our prospective, randomized, controlled monocentric trial [A prospective, randomized, controlled, double-blinded study investigating intraoperative temperature and postoperative pain course following gynecological laparoscopy-TePaLa (Temperature and Pain in Laparoscopy)].The part concerning postoperative pain has been published before [15]. This article describes the parts of the TePaLa trial concerning the patient's temperature during laparoscopy.…”
Section: Introductionmentioning
confidence: 99%